Analisis Performa Algoritma SPECK Pada Raspberry Pi - Panji Mansyur Ansyah; Mochammad Hannats Hanafi Ichsan; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cryptographic algorithms are logical steps for hiding messages from people who are not entitled to the message. Security in hardware is also very important when the values ​​generated from sensors and other processes are sent via the internet, the data is not easily known by third parties. The SPECK algorithm is the latest encryption algorithm created by the National Security Agency (NSA). SPECK block Cipher has 10 types of blocks consisting of the smallest 32 bits up to the largest 128 bit block. This research was conducted to determine the performance of the SPECK algorithm when applied to Raspberry Pi. In this study using data collection methods and testing carried out as much as 1024 times on each SPECK algorithm. SPECK that will be tested is SPECK block 128 bit size with key size 128 bits, 192 bits and 256 bits. The results of the study concluded that the processing time of the SPECK algorithm to encrypt and decrypt plaintext with an average time of 85920μs - 91073μs. RAM consumption for all algorithms requires 0.5% on the Raspberry Pi, the CPU is only used when the program runs at 2.6%. Data analysis calculations were tested by the Kruskal-Wallis method and produced data from the study experiencing significant differences from each encryption and decryption process on the SPECK block size 128 bit algorithm with 128-bit, 192-bit and 256-bit key variants.